Impact of aberrant left hepatic artery ligation on the outcome of liver transplantation. Issue 2 (29th January 2018) - Montalti, Roberto; Benedetti Cacciaguerra, Andrea; Nicolini, Daniele; Ahmed, Emad Alì; Coletta, Martina; De Pietri, Lesley; Risaliti, Andrea; Troisi, Roberto Ivan; Mocchegiani, Federico; Vivarelli, Marco
Abstract : The preservation of a graft's aberrant left hepatic artery (LHA) during liver transplantation (LT) ensures optimal vascularization of the left liver but can also be considered a risk factor for hepatic artery thrombosis (HAT). In contrast, ligation of an aberrant LHA may lead to hepatic ischemia with the potential risk of graft dysfunction and biliary complications. The aim of this study was to prospectively analyze the impact on the surgical strategy for LT of 5 tests performed to establish whether an aberrant LHA was an accessory or a replaced artery, thus leading to the design of a decisional algorithm. From August 2005 to December 2016, 395 whole LTs were performed in 376 patients. Five parameters were evaluated to determine whether an aberrant LHA was an accessory or a replaced artery. On the basis of our decision algorithm, an aberrant LHA was ligated during surgery when assessed as accessory and preserved when assessed as replaced. A total of 138 anatomical variants of hepatic arterial vascularization occurred in 120/395 (30.4%) grafts. Overall, the incidence of an aberrant LHA was 63/395 (15.9%). The LHA was ligated in 33 (52.4%) patients and preserved in 30 (47.6%) patients. After a mean follow‐up period of 50.9 ± 39.7 months, the incidence of HAT, primary nonfunction, early allograft dysfunction, biliary stricture or leaks, and overall survival was similar in the 2 groups. In conclusion, once shown to be an accessory, an LHA can be safely ligated without clinical consequences on the outcome of LT. Liver Transplantation 24 204–213 2018 AASLD.